Pioneers of Cardiac Surgery - Stoney, William S., 1928- (Book collections on Project MUSE., 2008)
This book is a history of cardiac surgery in the words of the first generation of surgeons. Heart operations today are quite common and relatively low-risk, but in the beginning it was just the opposite. Cardiac operations were reserved for desperately ill patients. The author documents this dramatic transition with profiles of 38 surgeons who were active between 1940 and 1985. The profiles are edited transcripts of interviews videotaped between 1996 and 2004. They tell of the development of new techniques such as the "blue baby operation," the first heart-lung machine, the first artificial heart valve, and the first coronary bypass operation. They also tell the unusual life stories of the surgeons and allude to professional and institutional rivalries. A particularly valuable part of the book is the author's brief history of cardiac surgery, designed to orient the reader for reading the profiles that follow. - Publisher.